XÂY DỰNG CƠ SỞ SỐ LIỆU TỪ THẠCH HỌC TẠI VIỆT NAM - Lan, Lưu Thị Phương (Vietnam Journal of Earth Sciences, 2005)
A magnetic petrology database (MPDB) is very importance for realistic interpretation satellite, as well as aeromagnetic and ground magnetic anomalies. The NASA open Web of MPDB allow the geomagnetic community to access; to use and to contribute more. This paper introduces about NASA’s established world’s MPDB and possibility these database to use and to contribute Vietnamese MPDB into the world’s ones. Database includes 6 related tables : Sample_ description, petrophysical_data, petrochemical_data, reference, tectonics, Satellite_Magnetic_Anomaly. All the measured values · are archived in two tables petrophysical_data and petrochemical_data.